Black thread scale, Ischnaspis longirostris (Signoret) (Insecta: Hemiptera: Diaspididae) - Adriana Espinosa; Amanda Hodges; Greg Hodges; Catharine Mannion (EDIS, 2009)
EENY-450, a 4-page illustrated fact sheet by Adriana Espinosa, Amanda Hodges, Greg Hodges, and Catharine Mannion, is part of the Featured Creatures collection. It describes this one of the most serious armored scale pests worldwide, attacking over 50 families of host plants — its distribution, field characteristics, life cycle, hosts, plant damage and economic importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, June 2009.